2016
DOI: 10.1159/000453198
|View full text |Cite
|
Sign up to set email alerts
|

The Clinicopathological Significance of Epigenetic Silencing of VHL Promoter and Renal Cell Carcinoma: A Meta-Analysis

Abstract: Background/Aims: Von Hippel-Lindau gene (VHL) has been reported as a tumor-suppressor gene in some cancers. However, the association between VHL promoter hypermethylation and renal cell carcinoma (RCC) remains to be clarified. We are the first to systematically integrate published papers to assess the role of hypermethylated VHL in RCC. Methods: The potential relevant papers were searched via PubMed, Embase, EBSCO, CNKI, and Wanfang databases. The overall odds ratio (OR) and corresponding 95% confidence interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Consistent with our results, in a recent elegant study, Chen et al shows that miR-30a-5p expression is restricted and the reduced expression of mir-30a-5p promotes ccRCC prognosis [31]. Von Hippel-Lindau gene (VHL) has been reported as a tumor-suppressor gene, which is associated with ccRCC [32, 33]. Mathew et al has found that miR-30a-3p is repressed in the VHL deficient ccRCC tumors [34].…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our results, in a recent elegant study, Chen et al shows that miR-30a-5p expression is restricted and the reduced expression of mir-30a-5p promotes ccRCC prognosis [31]. Von Hippel-Lindau gene (VHL) has been reported as a tumor-suppressor gene, which is associated with ccRCC [32, 33]. Mathew et al has found that miR-30a-3p is repressed in the VHL deficient ccRCC tumors [34].…”
Section: Discussionsupporting
confidence: 89%
“…A large number of RCC patients are diagnosed at late and advanced stages, and the prognosis is often poor [1-4]. It is therefore very important to search novel oncogenes or therapeutic target proteins [7, 8], and to develop more effective anti-RCC strategies [1-4]. …”
Section: Introductionmentioning
confidence: 99%
“…The most common metabolic phenotype associated with cancer is the Warburg effect, which consists of increased glycolysis in the presence of oxygen [6]. In the case of RCC, several known oncogenes, including fumarate hydratase (FH), succinate dehydrogenase B (SDHB) and succinate dehydrogenase D (SDHD) are involved in abnormal glucose metabolism [7][8][9]. However, tumour cells exhibit not only an increased demand for glucose but also an increased dependence on other metabolic substances, such as acetate [10].…”
Section: Introductionmentioning
confidence: 99%